the effect of ozonated olive oil on the number of neutrophil cells in the gingiva of male Wistar rats experiencing periodontitis (in vivo) - Anwaristi, Aprilia Yuanita; Cahyani, Cahyani; Faizah, Ariyani; Fauziyah, Nida Faradisa; Arifin, Dani Fajar; Hidayanti, Nur; Lestari, Cindy (Odonto : Dental Journal, 2024)
Background: Periodontal tissue, comprising gingiva, periodontal ligament, cementum, and alveolar bone, supports and surrounds teeth. Periodontitis, an inflammation affecting these tissues, manifests through gingival inflammation, pocket formation, and loss of attachment and bone.Purpose: This research aims to investigate whether ozonated olive oil influences neutrophil cell levels in the gingiva of male Wistar rats with periodontitis.Method: Employing a posttest-only control group design, this laboratory study included 24 male Wistar rats with concentrated periodontitis divided into six groups based on the day of observation. Histological analysis was conducted on days 1, 3, and 5, with three control groups and treatment groups.Result: The hypothesis test revealed a significant difference in neutrophil cell count between the ozonated olive oil treatment group and the control group (p < 0.05). The treatment group exhibited superior outcomes compared to control and other treatment groups, as confirmed by the LSD Post Hoc Test (p < 0.05).Conclusion: Administration of ozonated olive oil can influence neutrophil cell involvement in periodontitis healing among male Wistar rats, suggesting its potential therapeutic efficacy